Comparison of fetal and maternal complication in twin and singleton pregnancies - Z Basirat; M Haji Ahmadi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2006)
BACKGROUND AND OBJECTIVE: Reflecting the wide variability of assisted reproduction technologies, the incidence of twin and higher order multiple gestation is increased which associated with complications and prenatal and maternal morbidity and mortality. The purpose of this study was to compare fetal and maternal complication in twin and singleton pregnancies. METHODS: This prospective study was performed on 108 twin pregnant women (case group) and 201 singleton pregnant women who referred to Babol Yahyanejad hospital during 2001-2003. Data related to patients were recorded in a questionnaire and the complication rate in both groups was compared. T-test and fishers exact test were used when appropriated. FINDINGS: Frequency of twin pregnancy was 1.4%. Preterm delivery was 60.2% in twin and 2.7% in singleton (p<0.05). Low birth weight and growth retardation was in 45.8% and 38.4% of twin and 7.5% and 10% of singleton, respectively. It was statistically significant (p<0.05). Frequency of placental abruption, previa, preeclampsia, fetal anomaly and death were not statistically significant.CONCLUSION: Results show that fetal complications such as preterm delivery, growth retardation and low birth weight were seen with higher frequency in twin pregnancies compared to singleton pregnancies. Since, this may cause high prenatal morbidity and mortality, therefore more attention is required to reduce complication.